n → ∞ lim ⎝ ⎜ ⎛ i = 0 ∏ 2 n ( i 2 n ) ⎠ ⎟ ⎞ 4 n 3 − n 2 n − 1 = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
This only gives 2 as an upper bound to the limit (assuming it to exist). You also need to show a lower bound.
nice solution, but i used table on that problem
This isn't a solution. If you want to say something, please add this as a comment to my solution!
there is this same question but with my method it is coming (e)^(1/2) Plz help.
Problem Loading...
Note Loading...
Set Loading...
We know 2 2 n = i = 0 ∑ 2 n ( i 2 n )
We have by A.M - G.M Inequality:
2 n + 1 i = 0 ∑ 2 n ( i 2 n ) ≥ ( i = 0 ∏ 2 n ( i 2 n ) ) 2 n + 1 1
⇒ 2 n + 1 2 2 n ≥ ( i = 0 ∏ 2 n ( i 2 n ) ) 2 n + 1 1
⇒ ( 2 n + 1 2 2 n ) 2 n 1 ≥ ( i = 0 ∏ 2 n ( i 2 n ) ) 2 n ( 2 n + 1 ) 1
⇒ 2 ≥ ( 2 n + 1 ) 2 n 1 ( i = 0 ∏ 2 n ( i 2 n ) ) 2 n ( 2 n + 1 ) 1
Therefore, when n tends to ∞ ,
n → ∞ lim ( 2 n + 1 ) 2 n 1 ( i = 0 ∏ 2 n ( i 2 n ) ) 2 n ( 2 n + 1 ) 1 = n → ∞ lim ⎝ ⎛ i = 0 ∏ 2 n ( i 2 n ) ⎠ ⎞ 4 n 3 − n 2 n − 1 = 2